Isosexual precocity in girls - M. Suttan Assin (Indonesian Pediatric Society, 1984)
Puberty is considered precocious when the onset takes place prior to eight years of age. lsosexual precocious puberty indicates that sexual development has occurred appropriate io the individual's phenotype. This can be a) true sexual or b) pseudosexual. In true sexual precocity there is a premature activation of hypothalamic-pituitary axis, while pseudosexual precocity is due to disease of the gonads or adrenal glands or, rarely, other hormone producing tissues. Incomplete sexual development can be ''premature thelarche'' or